Structure and soft magnetic properties of nanocrystalline Fe73.5Nb2Ta1Si13.5B9Cu1 alloy ribbons - Nguyen Ngoc, Dinh; Nguyen Quang, Hoa; Nguyen Duy, Thien; Nguyen Van, Dung; Tran Vinh, Thang; Tran Thi, Ngoc Anh; Do Thi, Kim Anh; Nguyen The, Nghia; Bach Thanh, Son; Vuong, Hiep (Communications in Physics, 2025)
The crystal structure and soft magnetic properties of thermomagnetic annealed \(\text{Fe}_{73.5}\text{Nb}_{2}\text{Ta}_{1}\text{Si}_{13.5}\text{B}_{9}\text{Cu}_{1}\) alloy ribbons prepared by rapid cooling were investigated. X-ray diffraction results showed that the as-cast alloy strips had a completely amorphous structure, while the annealed samples formed \(α\)-Fe (Si) nanocrystals with sizes ranging from 8 to 11 nm. Differential scanning calorimetry analysis of the as-cast samples indicated an exothermic crystallization peak at 515\(^{°}\)C of the first crystallization stage corresponding to the formation of the \(α\)-Fe (Si) crystalline phase. The as-cast ribbon samples were annealed at 500\(^{°}\)C for 30, 40, and 50 minutes and in a saturation magnetic field of 10 Oe. The crystallinity of the alloy ribbons thermomagnetically annealed at 500\(^{°}\)C for 30 min was determined by DSC analysis to be 42%. The optimum annealing time at 500\(^{°}\)C in a saturated magnetic field for the amorphous alloy ribbons to achieve the best magnetic properties was 40 minutes. Under that condition, the \(α\)- Fe (Si) phase crystallized completely, and the material exhibited excellent soft magnetic properties, with a saturation induction of \(\text{B}_{s} = 1.45\) T, coercivity \(\text{H}_{c} = 0.015\) Oe, and maximum permeability \(μ_{\text{max}} = 551,500\).